A mulher na produção têxtil portuguesa tardo-medieval - Joana Sequeira; Arnaldo Sousa Melo (Medievalista)
Through the analysis of generic and individual references on the occupation of women in the textile sector, this article will look to define the role of women at each stage of production (fiber preparation, spinning, weaving, finishing processes, manufacture of clothing and trade/organization of production).